Aportes de las controversias científicas y la resolución de problemas a la construcción del conocimiento del concepto enlace químico para docentes en formación (2012)
In this article are presented partial results of the use of the scientific controversy and resolution of problems in the design and implementation of a teaching unit about the concept of chemical bonding, as part of a research project conducted in the Undergraduate Curriculum Project in Chemistry Faculty of Science and Education of the University Francisco José de Caldas. In this paper we develop aspects such as: why are used Problem Solving and Scientific Controversy as teaching methodology for teachers in training, and the history of science as a central focus of both methodologies, we show results project phases and prospects of the remaining phases that are still developing